Cobalt (oxy)hydroxide nanosheet arrays with exceptional porosity and rich defects as a highly efficient oxygen evolution electrocatalyst under neutral conditions. Issue 17 (11th April 2019) - Chen, Minqi; Xie, Yanyu; Wu, Jun-Xi; Huang, Huanfeng; Teng, Jun; Wang, Dawei; Fan, Yanan; Jiang, Ji-Jun; Wang, Hai-Ping; Su, Cheng-Yong
Abstract : Highly porous and defective cobalt (oxy)hydroxide nanosheet arrays rank the best cobalt-based noble-metal-free oxygen evolution electrocatalyst under neutral conditions. Abstract : An oxidation-mediated defect and porosity enrichment strategy is developed for the synthesis of a new electrocatalyst consisting of cobalt (oxy)hydroxide nanosheet arrays (denoted as CoO x H y NSAs) grown on carbon cloth (CC), which feature a 3D hierarchical nanostructure with exceptional porosity and rich defects. The CoO x H y /CC shows exceptional activity and stability for the oxygen evolution reaction under neutral conditions, as indicated by its high current density of 38 mA cm −2 at 1.8 V, small Tafel slope of 121 mV dec −1, low overpotential of 430 mV, and 24 h durability at 10 mA cm −2 in 0.1 M phosphate buffer solution (PBS).